KOMPARASI FAKTOR-FAKTOR YANG MEMPENGARUHI INFLASI DI INDONESIA DAN SINGAPURA - Maulidya, Alifa Nurma; Rahim, Abd; Astuty, Sri; Bado, Basri; Hastuti, Diah Retno Dwi (Airlangga Journal of Innovation Management, 2025)
This study aims to analyze the factors affecting inflation in Indonesia and Singapore in the period 2000-2023 using a comparative approach. A quantitative approach was used, employing time series data from the World Bank, BPS (Statistics of Indonesia), and the Singapore Department of Statistics. The analysis method used is multiple linear regression to determine the effect of independent variables (quantity of money, interest rate, exchange rate, and economic growth) and dependent variables (inflation) simultaneously and partially. The results of this study show that independent variables have a simultaneous effect on dependent variables in Indonesia, while in Singapore, they do not. Meanwhile, in part, the quantity of money has a significant negative effect on inflation in Indonesia. Meanwhile, in part, the exchange rate has a negative and significant effect on inflation in Singapore. A comparison of the coefficients and adj. R² values reveal a higher level of sensitivity of inflation to quantitative monetary policy in Indonesia, while Singapore shows inflation resilience through a policy framework centered on exchange rates. These results confirm the differences in the structure and effectiveness of monetary policy, as well as their implications for the formulation of price stabilization strategies in both countries.